A preparation process of composite ceramic material
By using the use of high temperature -resistant composite cross -linked agents and anti -ultraviolet additives during the preparation of composite ceramic materials, the problem of insufficient patience, poor anti -ultraviolet ability, and lack of pollution -proof ability at high temperature at high temperature, lack of material anti -ultraviolet ability, and lack of pollution prevention capacity, and realized the materials. Excellent performance and long -term use in a variety of environments.
Patent Information
- Application Number
- CN202411562119.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-11-05
AI Technical Summary
Composite ceramicized materials have insufficient resistance, poor UV resistance and lack of anti-fouling ability at high temperatures, which limits their long-term use in various environments.
By preparing high -temperature composite cross -linked agents and anti -ultraviolet adding materials, and adding it to the preparation of composite ceramic materials, it improves the high temperature resistance, ultraviolet capacity and anti -slimness performance of the material.
The excellent performance of composite ceramic materials in a variety of environments, including high temperature resistance, anti -ultraviolet, corrosion resistance and pollution prevention, extending the service life of materials.
Smart Images

Figure CN119060530B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a preparation process of a composite ceramic material. Background Art
[0002] Composite ceramic material is a polymer material formed by mixing thermoplastic resin with ceramic filler. It is widely used in wire and cable, chemical industry, light industry and construction. Thermoplastic polyurethane material has good elasticity, low temperature resistance, wear resistance and oil resistance. It is one of the commonly used materials for preparing composite ceramic materials. However, ordinary thermoplastic polyurethane materials have poor high temperature resistance, corrosion resistance, UV resistance and anti-fouling ability. This makes it difficult for the prepared composite ceramic material to meet the long-term use requirements in various environments, greatly limiting its application areas.
[0003] The patent with announcement number CN112210156B discloses a ceramic halogen-free flame-retardant polymer composite material and its application, which is prepared by a polymer substrate, a ceramic filler, a halogen-free flame retardant, a synergistic flame retardant, a plasticizer, an antioxidant, and a cross-linking agent. The ceramic halogen-free flame-retardant polymer composite material prepared by this patent can form a dense ceramic product at high temperature, has good high-temperature strength and flame retardant properties, and also has good mechanical properties at room temperature. Although the ceramic halogen-free flame-retardant polymer composite material prepared in this patent can withstand high temperatures, it has insufficient anti-ultraviolet and anti-corrosion capabilities when used at room temperature. When used outdoors, ultraviolet rays will accelerate the aging process of the material, and it is difficult to exist stably in a corrosive medium for a long time, shortening the service life. At the same time, when this material is used, the accumulation of stains will make it difficult to clean the material. Summary of the invention
[0004] The purpose of the present invention is to provide a preparation process of a composite ceramic material, which solves the following technical problems: (1) the high temperature resistance and corrosion resistance of the composite ceramic material need to be improved; (2) the composite ceramic material has weak UV resistance and no anti-fouling ability.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A preparation process of a composite ceramic material comprises the following preparation steps:
[0007] Step 1: Mix polyether polyol and toluene diisocyanate, stir at 35-45° C. and 500-600 r / min for 10-15 min, add organic tin catalyst, high temperature resistant composite cross-linking agent, anti-fouling and anti-ultraviolet additives, heat to 45-55° C., stir at 500-600 r / min for 3-5 min, and obtain a mixed solution;
[0008] Step 2: placing the mixed solution in a mold, heating it to 100-110° C. under vacuum conditions for 48-52 hours to obtain a modified thermoplastic polyurethane elastomer;
[0009] Step 3, placing the modified thermoplastic polyurethane elastomer, halloysite nanopowder, low softening point glass powder, mica powder, plasticizer, and antioxidant in a high-speed mixer, and fully mixing them at a speed of 200-300 r / min for 1-1.5 hours to obtain a mixture;
[0010] Step 4: Place the mixed material in a twin-screw extruder, set the screw speed to 300-500 r / min, the extrusion temperature to 180-190° C., melt-extrude and granulate to obtain a composite ceramic material.
[0011] Furthermore, the organic tin catalyst is any one of dibutyltin dilaurate and stannous octoate.
[0012] Furthermore, the plasticizer is any one of diisononyl phthalate, dioctyl phthalate, and epoxidized soybean oil; and the antioxidant is any one of antioxidant 1010, antioxidant 5057, and antioxidant 136.
[0013] Furthermore, the preparation method of the high temperature resistant composite cross-linking agent comprises the following steps:
[0014] S1: placing bismaleimide resin in xylene, mixing and stirring thoroughly, adding 3-hydroxy-1-methacryloyloxyadamantane and an initiator, heating to 55-65° C. for reaction for 6-8 hours, and collecting the product after reduced pressure distillation to obtain a modified bismaleimide resin;
[0015] S2: Place the modified bismaleimide resin and glycidyl furfural ether in dimethyl sulfoxide and mix them thoroughly, add a catalyst, heat to 80-85°C and react for 8-10 hours, collect the product after reduced pressure distillation, and obtain a high temperature resistant composite cross-linking agent.
[0016] In this scheme, under the action of an initiator, the double bond in the bismaleimide resin structure undergoes a free radical polymerization reaction with the allyl group in the 3-hydroxy-1-methacryloyloxyadamantane structure to obtain a modified bismaleimide resin, and then under the action of a catalyst, the hydroxyl group in the modified bismaleimide structure undergoes a ring-opening reaction with glycidyl furfuryl ether to obtain a high-temperature resistant composite cross-linking agent; the high-temperature resistant composite cross-linking agent has hydroxyl groups at both ends of the structure, and the high-temperature resistant bismaleimide segment in the structure can produce mutual entanglement with the polyurethane polymer segment in the preparation process of the modified thermoplastic polyurethane elastomer, and at the same time, the adamantane structure and the furan ring with good heat resistance are embedded in the entangled structure, and the three produce a synergistic effect to jointly enhance the high-temperature resistance of the modified thermoplastic polyurethane elastomer, and due to the furan ring contained in its structure, the modified thermoplastic polyurethane elastomer can also be given additional corrosion resistance, so that the prepared composite ceramic material can have excellent high-temperature resistance and corrosion resistance, thereby meeting the use requirements in various environments.
[0017] Furthermore, in step S1, the initiator is any one of benzoyl peroxide and dicumyl peroxide.
[0018] Furthermore, in step S2, the catalyst is boron trifluoride etherate.
[0019] Furthermore, the preparation method of the antifouling and anti-ultraviolet additive comprises the following steps:
[0020] SS1: polymethyl vinyl ether maleic anhydride is placed in toluene, and after being fully mixed, perfluorobutyl ethyl alcohol and p-toluenesulfonic acid are added, the temperature is raised to react, and the product is collected after reduced pressure distillation to obtain modified polymethyl vinyl ether maleic anhydride;
[0021] SS2: Place modified polymethyl vinyl ether maleic anhydride in N,N-dimethylformamide, add nano titanium dioxide, and disperse ultrasonically for 15-20 minutes. Then heat to 100-105°C and stir thoroughly for 2-4 hours. After cooling to room temperature, filter, wash, and dry to obtain the anti-fouling and anti-ultraviolet additive.
[0022] In this scheme, under the action of p-toluenesulfonic acid, the maleic anhydride group in the polymethyl vinyl ether maleic anhydride structure reacts with the hydroxyl group in the perfluorobutyl ethyl alcohol structure to obtain a modified polymethyl vinyl ether maleic anhydride containing a carboxyl group in the structure, and then the modified polymethyl vinyl ether maleic anhydride containing a carboxyl group in the structure interacts with the hydroxyl group on the surface of the nano titanium dioxide to obtain an antifouling and anti-ultraviolet additive. This kind of antifouling and anti-ultraviolet additive uses nano titanium dioxide as the core, which can effectively enhance the antifouling ability and anti-ultraviolet ability of the composite ceramic material. At the same time, the organic matter coated on its surface has a perfluorinated chain segment, low surface energy, and a self-cleaning effect. It can produce a synergistic effect with nano titanium dioxide, greatly enhancing the antifouling ability of the composite ceramic material. At the same time, this kind of perfluorinated chain segment can also produce a synergistic effect with the furan ring in the high temperature resistant composite cross-linking agent, effectively enhancing the corrosion resistance of the composite ceramic material, so that it can meet the use requirements of various fields and have a long service life.
[0023] Furthermore, in step SS1, the temperature of the temperature-raising reaction is 75-85° C., and the time is 3-5 hours.
[0024] Furthermore, in step SS2, the particle size of the nano titanium dioxide is 80-300 nm.
[0025] Beneficial effects of the present invention:
[0026] The present invention prepares a high-temperature resistant composite cross-linking agent and an anti-fouling and anti-ultraviolet additive in the preparation process of the composite ceramic material, so that the composite ceramic material has excellent high-temperature resistance, corrosion resistance, anti-ultraviolet resistance and anti-fouling and self-cleaning properties, so that it can meet the use requirements in a variety of environments and have a long service life.
[0027] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0029] Figure 1 This is a graph showing the sedimentation rates of nano-titanium dioxide and anti-fouling and anti-ultraviolet additives in acetone in an embodiment of the present invention. DETAILED DESCRIPTION
[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] The preparation methods of the antifouling and anti-ultraviolet additives and the high temperature resistant composite crosslinking agent in the following embodiments and comparative examples of the present invention are as follows:
[0032] 1. Preparation of high temperature resistant composite cross-linking agent
[0033] S1: 2.6 g of bismaleimide resin was placed in 60 ml of xylene, and after sufficient mixing and stirring, 2.2 g of 3-hydroxy-1-methacryloyloxyadamantane and 0.5 g of benzoyl peroxide were added, and the temperature was raised to 55° C. for reaction for 6 h, and the product was collected after reduced pressure distillation to obtain a modified bismaleimide resin;
[0034] S2: 3 g of modified bismaleimide resin and 2.6 g of glycidyl furfural ether were placed in 80 ml of dimethyl sulfoxide and mixed thoroughly, 0.8 g of boron trifluoride ether was added, the temperature was raised to 80°C for reaction for 8 h, and the product was collected after reduced pressure distillation to obtain a high temperature resistant composite cross-linking agent.
[0035] The 5E-CHONS2400 element analyzer was used to test the nitrogen and oxygen contents in the modified bismaleimide resin and the high-temperature resistant composite cross-linking agent. The test showed that the nitrogen content in the modified bismaleimide was 9.45%, and the oxygen content was 36.87%; while the nitrogen content in the high-temperature resistant composite cross-linking agent was 8.57%, and the oxygen content was 39.94%; compared with the modified bismaleimide, it can be seen that the nitrogen content in the high-temperature resistant composite cross-linking agent was slightly reduced, and the oxygen content was increased, which was caused by the ring-opening reaction between the modified bismaleimide resin and glycidyl furfuryl ether.
[0036] 2. Preparation of anti-fouling and anti-UV additives
[0037] SS1: 3 g of polymethyl vinyl ether maleic anhydride was placed in 60 ml of toluene, and after thorough mixing, 3.2 g of perfluorobutyl ethyl alcohol and 0.3 g of p-toluenesulfonic acid were added, and the temperature was raised to 75°C for reaction for 3 h. The product was collected after reduced pressure distillation to obtain modified polymethyl vinyl ether maleic anhydride;
[0038] SS2: Place 3.5g of modified polymethyl vinyl ether maleic anhydride in 80ml of N,N-dimethylformamide, add 2g of nano titanium dioxide with a particle size of 80nm, and after ultrasonic dispersion for 15min, heat to 100℃ and stir thoroughly for 2h. After cooling to room temperature, filter, wash and dry to obtain the anti-fouling and anti-ultraviolet additive.
[0039] 2g of nano titanium dioxide and 2g of antifouling and anti-ultraviolet additives were placed in 150ml of acetone, and ultrasonically dispersed for 30min before a sedimentation experiment. Figure 1 It can be seen that the sedimentation rate of nano titanium dioxide in acetone is relatively fast and reaches sedimentation equilibrium within 3 hours; while the sedimentation rate of anti-fouling and anti-UV additives is slow and reaches sedimentation equilibrium within 10 hours; compared with the sedimentation rate of nano titanium dioxide, the sedimentation rate of anti-fouling and anti-UV additives is slow, indicating that the anti-fouling and anti-UV additives have better dispersibility in acetone, which is caused by the surface of the anti-fouling and anti-UV additives being coated with organic matter. Example 1
[0040] Preparation of composite ceramic materials
[0041] Step 1: Mix 50 parts of polyether polyol and 30 parts of toluene diisocyanate, stir at 35°C and 500 r / min for 10 min, add 0.5 parts of dibutyltin dilaurate, 7 parts of high temperature resistant composite cross-linking agent, and 6 parts of anti-fouling and anti-ultraviolet additives, heat to 45°C, stir at 500 r / min for 3 min, and obtain a mixed solution;
[0042] Step 2: Place the mixed solution in a mold, heat it to 100° C. under vacuum conditions and heat it for 48 hours to obtain a modified thermoplastic polyurethane elastomer.
[0043] Step 3, placing 60 parts of modified thermoplastic polyurethane elastomer, 8 parts of halloysite nanopowder, 10 parts of low softening point glass powder, 5 parts of mica powder, 1 part of diisononyl phthalate, and 1 part of antioxidant 1010 in a high-speed mixer, and mixing them thoroughly at a speed of 200 r / min for 1 hour to obtain a mixture;
[0044] Step 4: Place the mixed material in a twin-screw extruder, set the screw speed to 300 r / min, the extrusion temperature to 180° C., melt-extrude and granulate to obtain a composite ceramic material. Example 2
[0045] Preparation of composite ceramic materials
[0046] Step 1: Mix 60 parts of polyether polyol and 35 parts of toluene diisocyanate, stir at 40°C and 550 r / min for 12 min, add 0.8 parts of stannous octoate, 8 parts of high temperature resistant composite cross-linking agent, and 8 parts of anti-fouling and anti-ultraviolet additives, heat to 55°C, stir at 550 r / min for 4 min, and obtain a mixed solution;
[0047] Step 2: Place the mixed solution in a mold, heat it to 105° C. under vacuum conditions and heat it for 50 hours to obtain a modified thermoplastic polyurethane elastomer.
[0048] Step 3, placing 70 parts of modified thermoplastic polyurethane elastomer, 10 parts of halloysite nanopowder, 12 parts of low softening point glass powder, 7 parts of mica powder, 2 parts of dioctyl phthalate, and 1.5 parts of antioxidant 5057 in a high-speed mixer, and mixing them thoroughly at a speed of 250 r / min for 1.2 hours to obtain a mixture;
[0049] Step 4: Place the mixed material in a twin-screw extruder, set the screw speed to 400 r / min, the extrusion temperature to 185° C., melt-extrude and granulate to obtain a composite ceramic material. Example 3
[0050] Preparation of composite ceramic materials
[0051] Step 1: Mix 70 parts of polyether polyol and 40 parts of toluene diisocyanate, stir at 45°C and 600 r / min for 15 minutes, add 1 part of dibutyltin dilaurate, 10 parts of high temperature resistant composite cross-linking agent, and 9 parts of anti-fouling and anti-ultraviolet additives, heat to 55°C, and stir at 600 r / min for 5 minutes to obtain a mixed solution;
[0052] Step 2: Place the mixed solution in a mold, heat it to 110° C. under vacuum conditions and heat it for 52 hours to obtain a modified thermoplastic polyurethane elastomer.
[0053] Step 3, placing 80 parts of modified thermoplastic polyurethane elastomer, 12 parts of halloysite nanopowder, 14 parts of low softening point glass powder, 8 parts of mica powder, 3 parts of dioctyl phthalate, and 2 parts of antioxidant 136 in a high-speed mixer, and mixing them at a speed of 300 r / min for 1.5 hours to obtain a mixture;
[0054] Step 4: Place the mixed material in a twin-screw extruder, set the screw speed to 500 r / min, the extrusion temperature to 190° C., melt-extrude and granulate to obtain a composite ceramic material.
[0055] Comparative Example 1
[0056] Preparation of composite ceramic materials
[0057] Step 1: Mix 60 parts of polyether polyol and 35 parts of toluene diisocyanate, stir at 40°C and 550 r / min for 12 min, add 0.8 parts of stannous octoate and 8 parts of antifouling and anti-ultraviolet additives, heat to 55°C, stir at 550 r / min for 4 min, and obtain a mixed solution;
[0058] Step 2: Place the mixed solution in a mold, heat it to 105° C. under vacuum conditions and heat it for 50 hours to obtain a modified thermoplastic polyurethane elastomer.
[0059] Step 3, placing 70 parts of modified thermoplastic polyurethane elastomer, 10 parts of halloysite nanopowder, 12 parts of low softening point glass powder, 7 parts of mica powder, 2 parts of dioctyl phthalate, and 1.5 parts of antioxidant 5057 in a high-speed mixer, and mixing them thoroughly at a speed of 250 r / min for 1.2 hours to obtain a mixture;
[0060] Step 4: Place the mixed material in a twin-screw extruder, set the screw speed to 400 r / min, the extrusion temperature to 185° C., melt-extrude and granulate to obtain a composite ceramic material.
[0061] Comparative Example 2
[0062] Preparation of composite ceramic materials
[0063] Step 1: Mix 60 parts of polyether polyol and 35 parts of toluene diisocyanate, stir at 40°C and 550 r / min for 12 min, add 0.8 parts of stannous octoate and 8 parts of high temperature resistant composite cross-linking agent, heat to 55°C, stir at 550 r / min for 4 min, and obtain a mixed solution;
[0064] Step 2: Place the mixed solution in a mold, heat it to 105° C. under vacuum conditions and heat it for 50 hours to obtain a modified thermoplastic polyurethane elastomer.
[0065] Step 3, placing 70 parts of modified thermoplastic polyurethane elastomer, 10 parts of halloysite nanopowder, 12 parts of low softening point glass powder, 7 parts of mica powder, 2 parts of dioctyl phthalate, and 1.5 parts of antioxidant 5057 in a high-speed mixer, and mixing them thoroughly at a speed of 250 r / min for 1.2 hours to obtain a mixture;
[0066] Step 4: Place the mixed material in a twin-screw extruder, set the screw speed to 400 r / min, the extrusion temperature to 185° C., melt-extrude and granulate to obtain a composite ceramic material.
[0067] Comparative Example 3
[0068] Preparation of composite ceramic materials
[0069] Step 1: Mix 60 parts of polyether polyol and 35 parts of toluene diisocyanate, stir at 40°C and 550 r / min for 12 min, add 0.8 parts of stannous octoate, 8 parts of modified bismaleimide resin, and 8 parts of antifouling and anti-ultraviolet additives, heat to 55°C, stir at 550 r / min for 4 min, and obtain a mixed solution;
[0070] Step 2: Place the mixed solution in a mold, heat it to 105° C. under vacuum conditions and heat it for 50 hours to obtain a modified thermoplastic polyurethane elastomer.
[0071] Step 3, placing 70 parts of modified thermoplastic polyurethane elastomer, 10 parts of halloysite nanopowder, 12 parts of low softening point glass powder, 7 parts of mica powder, 2 parts of dioctyl phthalate, and 1.5 parts of antioxidant 5057 in a high-speed mixer, and mixing them thoroughly at a speed of 250 r / min for 1.2 hours to obtain a mixture;
[0072] Step 4: Place the mixed material in a twin-screw extruder, set the screw speed to 400 r / min, the extrusion temperature to 185° C., melt-extrude and granulate to obtain a composite ceramic material.
[0073] Comparative Example 4
[0074] Preparation of composite ceramic materials
[0075] Step 1: Mix 60 parts of polyether polyol and 35 parts of toluene diisocyanate, stir at 40°C and 550 r / min for 12 min, add 0.8 parts of stannous octoate, 8 parts of bismaleimide resin, and 8 parts of antifouling and anti-ultraviolet additives, heat to 55°C, stir at 550 r / min for 4 min, and obtain a mixed solution;
[0076] Step 2: Place the mixed solution in a mold, heat it to 105° C. under vacuum conditions and heat it for 50 hours to obtain a modified thermoplastic polyurethane elastomer.
[0077] Step 3, placing 70 parts of modified thermoplastic polyurethane elastomer, 10 parts of halloysite nanopowder, 12 parts of low softening point glass powder, 7 parts of mica powder, 2 parts of dioctyl phthalate, and 1.5 parts of antioxidant 5057 in a high-speed mixer, and mixing them thoroughly at a speed of 250 r / min for 1.2 hours to obtain a mixture;
[0078] Step 4: Place the mixed material in a twin-screw extruder, set the screw speed to 400 r / min, the extrusion temperature to 185° C., melt-extrude and granulate to obtain a composite ceramic material.
[0079] Comparative Example 5
[0080] Preparation of composite ceramic materials
[0081] Step 1: Mix 60 parts of polyether polyol and 35 parts of toluene diisocyanate, stir at 40°C and 550 r / min for 12 min, add 0.8 parts of stannous octoate, 8 parts of high temperature resistant composite cross-linking agent, and 8 parts of modified polymethyl vinyl ether maleic anhydride, heat to 55°C, stir at 550 r / min for 4 min, and obtain a mixed solution;
[0082] Step 2: Place the mixed solution in a mold, heat it to 105° C. under vacuum conditions and heat it for 50 hours to obtain a modified thermoplastic polyurethane elastomer.
[0083] Step 3, placing 70 parts of modified thermoplastic polyurethane elastomer, 10 parts of halloysite nanopowder, 12 parts of low softening point glass powder, 7 parts of mica powder, 2 parts of dioctyl phthalate, and 1.5 parts of antioxidant 5057 in a high-speed mixer, and mixing them thoroughly at a speed of 250 r / min for 1.2 hours to obtain a mixture;
[0084] Step 4: Place the mixed material in a twin-screw extruder, set the screw speed to 400 r / min, the extrusion temperature to 185° C., melt-extrude and granulate to obtain a composite ceramic material.
[0085] Performance Testing
[0086] The composite ceramic materials prepared in Examples 1 to 3 and Comparative Examples 1 to 5 were used as samples, and the Vicat softening temperature test was performed on the samples according to the reference standard GB / T1633-2000 to determine the high temperature resistance of the samples; the samples were placed in a UV aging box at an ultraviolet wavelength of 313 nm and an irradiance of 0.72 / m 2 After irradiation for 1 day, the samples were subjected to tensile strength test to determine the mechanical strength and UV resistance of the samples; the samples were placed in 2 mol / L hydrochloric acid solution and 2 mol / L sodium hydroxide solution for 10 hours, and the weight loss of the samples was counted. The weight loss rate was calculated according to the following formula: weight loss rate = (sample mass - sample mass after immersion) × 100% / sample mass, to determine the corrosion resistance of the samples; the water contact angle of the samples was tested using an SDC-80 contact angle meter to determine the antifouling ability of the samples; the specific test results are shown in the table below:
[0087]
[0088] It can be seen from the above table that the samples prepared in Examples 1 to 3 all have excellent high temperature resistance, UV resistance, corrosion resistance and anti-fouling performance. In the sample prepared in Comparative Example 1, no high temperature resistant composite cross-linking agent was added, and in the sample prepared in Comparative Example 2, no anti-fouling and anti-ultraviolet additives were added. In the sample prepared in Comparative Example 3, modified bismaleimide resin and anti-fouling and anti-ultraviolet additives were directly added. In the sample prepared in Comparative Example 4, bismaleimide resin and anti-fouling and anti-ultraviolet additives were directly added. In the sample prepared in Comparative Example 5, a high temperature resistant composite cross-linking agent and modified polymethyl vinyl ether maleic anhydride were directly added. It can be seen that the performance of the samples prepared in Comparative Examples 1 to 5 is not as good as that of the embodiments.
[0089] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0090] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.
Claims
1. A process for preparing a composite ceramic material, characterized in that: The method comprises the following preparation steps: Step 1: Mix polyether polyol and toluene diisocyanate, stir at 35-45° C. and 500-600 r / min for 10-15 min, add organic tin catalyst, high temperature resistant composite cross-linking agent, anti-fouling and anti-ultraviolet additives, heat to 45-55° C., stir at 500-600 r / min for 3-5 min, and obtain a mixed solution; Step 2: placing the mixed solution in a mold, heating it to 100-110° C. under vacuum conditions for 48-52 hours to obtain a modified thermoplastic polyurethane elastomer; Step 3, placing the modified thermoplastic polyurethane elastomer, halloysite nanopowder, low softening point glass powder, mica powder, plasticizer, and antioxidant in a high-speed mixer, and fully mixing them at a speed of 200-300 r / min for 1-1.5 hours to obtain a mixture; Step 4: placing the mixed material in a twin-screw extruder, setting the screw speed to 300-500 r / min, the extrusion temperature to 180-190° C., and melt-extruding and granulating to obtain a composite ceramic material; The preparation method of the high temperature resistant composite cross-linking agent comprises the following steps: S1: placing bismaleimide resin in xylene, mixing and stirring thoroughly, adding 3-hydroxy-1-methacryloyloxyadamantane and an initiator, heating to 55-65° C. for reaction for 6-8 hours, and collecting the product after reduced pressure distillation to obtain a modified bismaleimide resin; S2: placing the modified bismaleimide resin and glycidyl furfural ether in dimethyl sulfoxide and mixing them thoroughly, adding a catalyst, heating to 80-85° C. to react for 8-10 hours, and collecting the product after reduced pressure distillation to obtain a high temperature resistant composite cross-linking agent; The preparation method of the antifouling and anti-ultraviolet additive comprises the following steps: SS1: polymethyl vinyl ether maleic anhydride is placed in toluene, and after being fully mixed, perfluorobutyl ethyl alcohol and p-toluenesulfonic acid are added, the temperature is raised to react, and the product is collected after reduced pressure distillation to obtain modified polymethyl vinyl ether maleic anhydride; SS2: Place modified polymethyl vinyl ether maleic anhydride in N,N-dimethylformamide, add nano titanium dioxide, and disperse ultrasonically for 15-20 minutes. Then heat to 100-105°C and stir thoroughly for 2-4 hours. After cooling to room temperature, filter, wash, and dry to obtain the anti-fouling and anti-ultraviolet additive.
2. The process for preparing a composite ceramic material according to claim 1, characterized in that: The organic tin catalyst is any one of dibutyltin dilaurate and stannous octoate.
3. The preparation process of a composite ceramic material according to claim 1, characterized in that: The plasticizer is any one of diisononyl phthalate, dioctyl phthalate, and epoxidized soybean oil; the antioxidant is any one of antioxidant 1010, antioxidant 5057, and antioxidant 136.
4. The preparation process of a composite ceramic material according to claim 1, characterized in that: In step S1, the initiator is any one of benzoyl peroxide and dicumyl peroxide.
5. The process for preparing a composite ceramic material according to claim 1, characterized in that: In step S2, the catalyst is boron trifluoride etherate.
6. The process for preparing a composite ceramic material according to claim 1, characterized in that: In step SS1, the temperature of the temperature-raising reaction is 75-85° C. and the time is 3-5 hours.
7. The process for preparing a composite ceramic material according to claim 1, characterized in that: In step SS2, the particle size of the nano titanium dioxide is 80-300 nm.
Citation Information
Patent Citations
A ceramicizable halogen-free flame-retardant polymer composite material and its application
CN112210156B
High temperature resistant ceramic polyurethane foam composite and preparation method thereof
CN106349455A
Low-smoke flame-retarding ceramizable thermoplastic polyurethane elastomer composite material, preparation method and application thereof
CN107286636A